2016
DOI: 10.1037/pas0000277
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Family Law DOORS.

Abstract: When former spouses experience distress and dispute following separation, risks to well-being and to safety are heightened for all family members. Reliable family-wide risk screening is essential. The Family Law DOORS (Detection of Overall Risk Screen) is a 3-part screening framework to assist identification, evaluation, and response to safety and well-being risks in separated families. Uniquely, the Family Law DOORS screens for victimization and perpetration risks and appraises infant and child developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Although FL-DOORS was designed for clinical use, establishing the robustness of such a measure is crucial to accurate risk recognition and response. McIntosh et al (2016) found strong scale properties in FL-DOORS (n ϭ 660). Revalidation across large, diverse samples is important.…”
mentioning
confidence: 91%
“…Although FL-DOORS was designed for clinical use, establishing the robustness of such a measure is crucial to accurate risk recognition and response. McIntosh et al (2016) found strong scale properties in FL-DOORS (n ϭ 660). Revalidation across large, diverse samples is important.…”
mentioning
confidence: 91%
“…On the other hand, risk is not only understood in terms of damage to property but also in terms of the discontinuity generated during daily life. In this sense, risk is viewed from the perspective of both individual well-being and the safety of family, friends and community partners (McIntosh et al 2016 ; Zwetsloot et al 2017 ). In order to understand risk, social scientists must therefore integrate the concepts of property damage and threats to living conditions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To offer support to children and parents in the target group 4. To strengthen the child's participation The risk detection model FL-DOORS has been developed by a research team in Australia in cooperation with researchers in Canada and the United States (see McIntosh & Ralfs, 2012a, 2012bMcIntosh, Wells, & Lee, 2016;Wells, Lee, Li, Tan, & McIntosh, 2018). The aim of the FL-DOORS is to be a "doorway" to support and services.…”
Section: Coordinated Multidisciplinary Collaboration Teammentioning
confidence: 99%